Model Manajemen Keuangan Usaha Kecil Menengah dalam Upaya Merumuskan Strategi Manajemen Keuangan (Studi Kasus pada UMKM di Kecamatan Majalaya dan Kecamatan Ciparay Kab. Bandung) - Devi, Rizca Puspita (Jurnal Study and Management Research, 2023)
Tujuan_Small and Medium Enterprises (SMEs) is known all around the world as driving force for the promotion of an economy, this also happened in Indonesia that 96% SME’s survive through economy crisis in 1998 and being the life saver for Indonesia economy at that time, also for the time being SME gives contribution 60% to Indonesia economy growth and 97% job vacancies. Even though SMEs has big role in a country’s economy, but SMEs also known to be lack of personnel, lack of technology and have no segregation between business and owner’s personal interest. Desain/Metode_This research uses qualitative method to create model of small and medium enterprises to formulate financial management strategy. The data collected by in- depth interview, documentation and observation to six SME at Majalaya and Ciparay district. Temuan_The result model shows that SMEs in Majalaya and in Ciparay have different pattern in using equity, fund utilization, dividend claim and owner’s mentality aboutthe importance of financial management. Implikasi_Thus, this condition made unique model from both SME’s in Majalaya and Ciparay and also made certain strategy to get a good financial performance. Tipe Penelitian_Studi Empiris